Changes in the management of deep sternal wound infections: a 12‐year review. Issue 11 (1st September 2015) - Lonie, Sarah; Hallam, Jane; Yii, Michael; Davis, Philip; Newcomb, Andrew; Nixon, Ian; Rosalion, Alexander; Ricketts, Sophie
Abstract Background Deep sternal wound infection (DSWI) is a rare but life‐threatening complication following cardiac surgery associated with increased morbidity and mortality. Management of these patients has evolved over the years and can include sternal rewiring, mediastinal irrigation, negative‐pressure wound therapy (NPWT) dressing or repair with flaps. We reviewed changes in our management of DSWI and outcomes. Methods Using the Australian and New Zealand Society of Cardiac and Thoracic Surgeons database, 5472 underwent cardiac surgery at St Vincent's Hospital, Melbourne, and 42 were identified as developing DSWI requiring re‐operation between June 2002 and September 2014. Data were collected pertaining to risk factors for DSWI, management strategies and outcomes. Patients were compared from a period prior to NPWT dressing use (June 2002–February 2006, n = 14) and since the NPWT has been used regularly in the management of DSWI (from March 2006, n = 28). Patients were also compared based on the requirement for flap closure of their sternal wound. Results Because of the widespread use of NPWT dressings, there is a trend towards fewer sternal infections requiring flap closure (25 versus 42.8%) and less post‐operative complications after definitive closure (7.1 versus 28.6%). Before and after widespread NPWT use, patients require similar number of re‐operations before closure and have no significant differences in time to definitive closure or length of hospital stay. Conclusion The use of NPWT dressings as a bridge to definitive closure may reduce the need for more burdensome flap reconstruction, does not delay definitive reconstruction or prolong hospital stay and may reduce post‐reconstruction complications requiring re‐operation.